Exploring Students' Obstacle in English Speaking (Research Conducted at English Language Educational Study Programme) - Fadlan Mokodompit; Rasuna Rasid Talib; Haris Danial (Invention: Journal Research and Education Studies, 2025)
This research aims to identify and describe the specific obstacles encountered by English Language Education students at Gorontalo State University (UNG) in developing their speaking proficiency. The study employed a qualitative approach, utilizing questionnaires (Likert scale) and semi-structured interviews with 4th-semester students. The findings revealed that students face multi-faceted challenges categorized into Linguistic, Personal, Environmental, and Social problems. The dominant obstacles were Linguistic Problems (81% agreement), driven primarily by Mother Tongue Interference and difficulties in choosing appropriate words and maintaining fluency. Personal Problems (70.4%), particularly anxiety and hesitation, were also highly significant, hindering active participation due to the fear of negative evaluation. Environmental Problems (77.4%) highlighted issues with the Teaching Method and limited opportunities for spontaneous speaking practice. Social Problems (67.9%) centered on the fear of committing mistakes and criticism from peers. The research concludes that speaking challenges in this context stem from a strong interplay between linguistic deficits and affective factors. Therefore, effective intervention must address both vocabulary/grammar mastery and psychological support by creating a highly communicative and anxiety-reducing learning environment.